ANALISIS TINGKAT KESEHATAN BANK BERDASARKAN ASPEK EARNING DALAM RASIO CAMEL PADA PT. BANK MUAMALAT - irwan, ade; Rahmah, Syahidah (Universitas Muhammadiyah Makassar, 2018)
The title of this research is the analysis of bank soundness based on earnings aspects in the camel ratio at PT. Bank Muamalat. The method used in conducting this research is by using the CAMEL method. This research was compiled along with the rapid growth of banks lately. The categories are healthy, fairly healthy, unhealthy, and unhealthy. This research was conducted at PT. Bank Muamalat. Data collected is a balance sheet and income statement. CAMEL analysis has five aspects, on this occasion the author has the aspect of earnings using the ratio of ROA (Return On Assets) and BOPO (Operating Expenses to Operating Income). Based on the results of research conducted at PT Bank Muamalat CAMEL value based on earnings aspects using the ROA ratio in 2013 in the amount of 0.44%, 2014 amounted to 0.15%, and in 2015 amounted to 0.19% so it was categorized in groups Not healthy. While using the BOPO ratio in 2013 to 2015 is always below 93.52% so it is categorized in the Healthy group.